Incarcerated foreign body in the vagina of a postmenopausal lady - Poojari, Vidyashree G.; Vasudeva, Akhila; Mundkur, Anjali S.; Kumar, Pratap (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Vaginal foreign bodies retained for long duration are uncommon in present day scenario. When a female presents with recurrent foul smelling vaginal discharge, foreign body should be suspected. Here is a report of foreign body in the vagina of a postmenopausal lady.